Infusing undergraduate research into historically black colleges and universities curricula - McClinton, Jeton (Bingley, U.K. : Emerald, 2015)
Undergraduate Research (UGR) is any creative effort undertaken by an undergraduate that advances the knowledge of the student in an academic discipline and leads to new scholarly insights or the creation of new knowledge that adds to the wealth of the discipline. Undergraduate research is valued and encouraged at several HBCUs; however, the history, implementation, nor progress has not been sufficiently published and disseminated nationally. Importantly, a great deal of learning occurs when undergraduate students conduct research and, of course, much of this learning does not happen during the traditional coursework. Research leads to better understanding of and deeper appreciation for the discipline. Further, it is contended that students' career goals and academic expectations are enhanced as a result of research participation. Extensive undergraduate research can increase access to PhD programs. From the voices of faculty mentors, student mentees and UGR program directors and program coordinators this volume describes the successes of programs across HBCUs and discusses how retention and graduation rates have been increased as a result of participation.
Evolution and impact of interdisciplinary STEM undergraduate research programs at North Carolina A&T State University / Guoqing Tang, Caesar R. Jackson -- Paradigm shift : infusing research into teaching and learning at Claflin University / Angela W. Peters, Verlie A. Tisdale -- Six years of undergraduate research experiences at Bennett College / Hyunju Oh -- Undergraduate research at the Timbuktu Academy and at LS-LAMP at Southern University and A&M College in Baton Rouge (SUBR) / Diola Bagayoko, Ella L. Kelley, LaShounda Franklin -- Undergraduate research programs can also be faculty development programs / Melissa A. Harrington ... [et al.] -- Undergraduate research for students majoring in pharmaceutical sciences leads to student success / Carla E. Oldham, Kevin P. Williams, Linda G. Love -- The impact of undergraduate research in STEM at Morgan State University on the production of doctoral degrees in engineering and the sciences / Jumoke Ladeji-Osias ... [et al.] -- Impact of STEM capstone undergraduate research courses at Saint Augustine's University / Doreen F. Cunningham ... [et al.] -- Building a cohesive curriculum to promote psychology majors' success in research methods and statistics courses / Alan Goble, Sara Wrenn, Santiba Campbell -- Surviving senior seminar research : helpful strategies for improving overall project performance / Kenny A. Hendrickson, Kula A. Francis -- Developing STEM scholars with vision : psychology plants seeds of excellence / Amber B. Hodges, Anita M. Wells.
Includes index.
Print version record
Keywords: Education -- Multicultural Education; Higher & further education, tertiary education; African American universities and colleges -- United States